2015
DOI: 10.3389/fnbeh.2015.00178
|View full text |Cite
|
Sign up to set email alerts
|

The role of the amygdala in the perception of positive emotions: an “intensity detector”

Abstract: The specific role of the amygdala remains controversial even though the development of functional imaging techniques has established its implication in the emotional process. The aim of this study was to highlight the sensitivity of the amygdala to emotional intensity (arousal). We conducted an analysis of the modulation of amygdala activation according to variation in emotional intensity via an fMRI event-related protocol. Monitoring of electrodermal activity, a marker of psychophysiological emotional percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 60 publications
(100 reference statements)
7
61
1
1
Order By: Relevance
“…The findings of the present study are also in accordance with previous studies with respect to other stimulus categories that showed that high as compared to low arousing emotional stimuli produced stronger amygdalar activation independent of stimulus valence (e.g., pictures, odors, and words; Hamann and Mao, 2002; Anderson et al, 2003; Sabatinelli et al, 2005; Winston et al, 2005; Straube et al, 2011b; Laeger et al, 2012; Bonnet et al, 2015). Taken these studies and our present study together, it can be concluded that the amygdala is a detector of subjective relevance of stimuli across different categories of stimuli, including faces.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the present study are also in accordance with previous studies with respect to other stimulus categories that showed that high as compared to low arousing emotional stimuli produced stronger amygdalar activation independent of stimulus valence (e.g., pictures, odors, and words; Hamann and Mao, 2002; Anderson et al, 2003; Sabatinelli et al, 2005; Winston et al, 2005; Straube et al, 2011b; Laeger et al, 2012; Bonnet et al, 2015). Taken these studies and our present study together, it can be concluded that the amygdala is a detector of subjective relevance of stimuli across different categories of stimuli, including faces.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of emotional pictures, amygdalar activation was found to be stronger for both positive and negative as compared to neutral pictures (e.g., Kensinger and Schacter, 2006; Kanske et al, 2011). Pictures with high arousal were found to yield enhanced activations in the amygdala, regardless of emotional valence (e.g., Phan et al, 2003; Sabatinelli et al, 2005; Fastenrath et al, 2014; Bonnet et al, 2015). For odors, Royet et al (2000) reported stronger amygdalar activation for pleasant and unpleasant as compared to neutral odors.…”
Section: Introductionmentioning
confidence: 99%
“…Rising sound intensity has been proposed as an elementary auditory warning cue (Neuhoff, 1998), and has been demonstrated to activate the right amygdala more than a comparable decline in sound intensity (Bach et al, 2008). This finding is compatible with findings in the visual modality associating the amygdala with emotional intensity detection (Bonnet et al, 2015), and more generally with emotional relevance detection (Sander et al, 2003a). …”
Section: Perception Of Emotional Non-verbal Vocalizationssupporting
confidence: 91%
“…The amygdala is not only activated by negative or aversive stimuli (LeDoux 2000), but is sensitive to the relative intensity of positive stimuli (Bonnet et al 2015). However, there also is evidence for the lateralization of amygdala function in the context of emotional processing.…”
Section: Discussionmentioning
confidence: 99%